UNPACKING SOCIAL INTERACTIONS IN PACKAGE TOURS: A FOCUS ON TOURIST-TO-TOURIST AND TOURIST-TO-TOUR GUIDE INTERACTIONS AND INFLUENCING FACTORS - Tran Truc Vien Pham (Tạp chí Khoa học Đại học Đà Lạt)
This study aims to comprehensively understand social interactions on package tours. Using a qualitative approach, combining interviews (n = 33) and field observations (n = 3) administered to Vietnamese package tourists, the study identified ten common forms of social interaction among tourists and eight common forms between tourists and tour guides. The majority of tourist-to-tourist interactions were found to be social-oriented, while most tourist-to-tour guide interactions were service-oriented. The study also found that factors influencing these interactions included tour guide performance, tourist personality, tourist needs, and situational factors on tours. The findings make a significant contribution to the literature on social interactions and offer valuable practical implications for tour marketing and management practitioners, particularly in their efforts to manage social interactions on tours and recovery package tours in the post-Covid era.